About the Leadership of Kakimbek Salikov In Karakalpakstan In 1984- 1989 - B.Ibragimov (Genius Journals, 2022)
The social activity of Kakimbek Salikov, who was the leader of Karakalpakstan during 1984-1989, is viewed in the given article. The author gives an objective description of the “reformation” and “cotton matter” periods on the basis of memoirs of K. Salikov's contemporaries
Keywords: Uzbekistan; Karakalpakstan; “reformation”; cotton matter